Population genetic analysis of 12 X-STR markers in Slovakia - Zdenko Červenák; Filip Červenák; Andrej Choma; Marián Baldovič; Soňa Masnicová (Taylor & Francis Group, 2023)
Background: During the last 20 years, X-chromosomal STR markers have become widely used in forensic genetics and paternity testing. Nevertheless, to exploit their full potential in any given population, a reliable reference dataset needs to be established. Since no relevant studies concerning these markers have been performed on the Slovak population so far, we decided to analyse several commonly used markers in this population. Aim: To create an informative set of Slovak population data concerning X-STR markers. Subjects and methods: We genotyped 378 individuals and analysed 12 loci (DXS10148, DX10135, DXS8378, DXS7132, DXS10079, DXS10074, DXS10103, HPRTB, DXS10101, DXS10146, DXS10134 and DXS742) localised in four distinct linkage groups. Results: Our analysis showed that the most informative marker is DXS10135 (PIC = 0,927) and the most informative linkage group (LG) is LG1 with 149 different haplotypes. This analysis also confirmed linkage disequilibrium for two pairs of markers (DX10101-DX10103 and DX10101-HPRTB) within LG3 in female samples. No statistically significant departure from HWE was observed for any locus. Moreover, the interpopulation comparison of 8 European populations based on haplotype frequencies showed no statistically significant FST values in any LG, except for LG2 in comparison with the German population. Conclusion: We created a haplotype database for forensic analyses and kinship testing in Slovakia, as well as the CE dataset which can be used to further increase the decision power in similar analyses in the future.